(untitled) - Lubar, Steven (Washington, D.C., 2001)
This is a wonderful journey into Americana hosted by the Smithsonian. The photography is perfect, and the text is lively and informative. "Legacies" is a real potpourri of American stuff, including Judy Garland's ruby slippers from "The Wizard of Oz", Warren Harding's pajamas, inauguration gowns of several first ladies, the stove- pipe hat Lincoln wore the night he was assassinated. the original star spangled banner, Kermit the Frog, the original Teddy bear, and much much more.
Keywords: Đặc điểm quốc gia, người Mỹ,Material culture,Văn hóa vật chất,National characteristics, American.,National characteristics, American; Collection and preservation,Thu thập và bảo quản; United States,Hoa Kỳ